KONSTRUKSI MAKNA PATH SEBAGAI MEDIA KOMUNIKASI INTERPERSONAL DALAM DUNIA SOSIAL VIRTUAL DI KALANGAN MAHASISWA - ", Sofiyyah; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of the Internet gave rise to a social networking site that Path now comes into a new social network that is loved by many people, including students. The use of social networking Path as a virtual communication media raises various meanings associated with students why they chose to use the Path as a social network that is privacy. This study aims to determine the motive, meaning features Path, meaning non-verbal symbols emoticons and the meaning of friendship on the user experience among students in communication science of university of Riau.This research method is a method of qualitative research with phenomenological approach. Informants in this study were 10 students of communication science, University of Riau who as active users of social networking Path selected using purposive technique. Data was collected through observation, interviews, and documentation. Data analysis technique includes data reduction, data presentation and conclusion and verification.The results indicate that the motive for using the Path as a virtual communication media among students consists of a Because motive namely are trend, follow and unique, while in order to motive are information and privacy. Making of features Path as media of communications among the students consists of Path as media for the exchange of information, Path as a medium to express feelings, Path as entertainment media, Path as a medium for chatting, and Path as a medium to express themselves. Meaning of emoticons in Path as a symbol of nonverbal interaction of virtual communication media among the students to describe the expression of sad, happy, and surprised. Meaning of friendship in Path as a virtual communication medium among the students that experience a positive relationship to expand friendshipnetwork without having to meet person directly, creating a community of like Path Group and communication science students can obtain information from the friendship that exist in Path, whereas negative friendship experiences such termination of friendships may occur as a result of the perceived discomfort and less comfortable with notice if there are other users who view his personal profile.Keywords : Construction Meaning, Path, phenomenological, symbolic interaction.